Root Resorption of the Permanent Central Incisor through Ectopic Eruption of the Maxillary Canine - Maria Pires Machado Paixão; Kelly Maria Silva Moreira; Ricardo Scarparo Navarro; Suzana Cavalcanti Monteiro de Oliveira; José Carlos Pettorossi Imparato; Juliana Braga Reis (Hindawi Limited, 2023)
Although ectopic eruption of the maxillary canine has a low prevalence, a late diagnosis can have serious consequences. A careful clinical examination, assisted with radiographic examination, ensures early diagnosis, facilitates planning, and minimizes possible adverse consequences. This study reports a case of ectopic eruption of the permanent maxillary canine, with complete root resorption of the central permanent incisor, the consequences of which caused functional, aesthetic, and psychological harms to the patient. The procedures used included canine ectopic remodeling of the ectopic canine in the central incisor and orthodontic correction, which treated the anomaly and rebuilt the patient's self-esteem.